Clausewitz versus terrorism : eradicating the threat of Al Qaeda using the Remarkable Trinity and Centre of Gravity concepts. - Lee, David Nai Kong. (2008)
This paper advocates that in the war on terrorism, there will be no quick fixes or magically conjured solutions to such complex and longstanding problems. A comprehensive approach with a cohesive strategy will still require time, resources and most of all political will and patience. Moreover, the struggle against terrorism is never-ending, our search for solutions and new approaches must thus be continuous and unyielding.